Critical Discourse Analysis of Mad for Makeup's Femvertising on Instagram Campaigns - Carvia Sances; Dhyan D. F. Payung; Virienia Puspita; Z. Hidayat (Budapest International Research and Critics University, 2022)
Since the last few years, the emergence of local Indonesian beauty brands has increased marketing strategies oriented toward women as the target market. The brands are advocating messages for women's empowerment in online campaigns known as femvertising was well received by the audience. This study aims to analyze Mad for Makeup, a local Indonesian beauty brand Instagram campaign using the Norman Fairclough approach. This research found advocacy aspects for the existence of women as part of the Indonesian cultural phenomenon. However, the profit-oriented nature of business always comes to the fore. Also, the analysis found contradictions that occur in the two values. Even Mad for Makeup is inconsistent with the continuity of the message of women's empowerment. The implications of the results of this study are also discussed, and recommendations for future research.